The stratigraphy and sedimentology of Middle and Late Eocene carbonates of the Nile Valley, Egypt: A basinal analysis. - Fathy Hussien Abdou Soliman (1988)
Carbonate sediments in the northern Nile Valley were subjected to stratigraphical and sedimentological studies which led to a complete basinal analysis. Initiation of this basin occurred in the early Late Eocene at 40 MY. A workable lithostratigraphy is developed to group the various Formations (Beni Suef, Birket Qarun, Saqqara, the Qurn, and the Wadi Hof) under one regional rock unit; the Middle Mokattam Unit. Biostratigraphical zonations were adapted, by means of nannoplankton and (both micro and larger) foraminifera, to date the strata as closely as possible and to achieve chronostratigraphical correlations. Onlap-offlap and facies interfingering relationships are recorded and discussed. The stratigraphical investigation has shown the presence of a depositional basin (Middle Mokattam basin) and detected its outline. Sedimentological studies and detailed modal analysis of carbonate grains have identified 12 major facies and 36 microfacies associations. These have clarified the depositional environments which occupied the basin. Careful basinal analysis, for both stratigraphical and sedimentological investigations, together with paleoecological determination of carbonate grains and communities, were used to reveal the basin configuration. Soft sediment deformation is also recorded and used to interpret the pattern of syndepositional subsidance which was controlled by rejuvenated deep-seated faults. Recurring uplift of the external northwestern block shaped the basin and controlled the depositional processes. This was responsible for an influx of residemented deposits derived either from nearby shelves or from adjacent paleohighs. The resedimented deposits formed deeply chajinelled fans and clastic barriers. The basin exhibits abundant evidence of synchronous tectonic uplift and sedimentation. Features such as growth femits, syn-sedimentary and syn-tectonic unconformities, debris and mass gravity flow deposits demonstrate a direct link between sedimentation and tectonism, and highlight the episodic nature of uplift in the external parts of the basin. This uplift resulted in the syn-sedimentary southward shifting of the depositional axis.